FAKTOR-FAKTOR YANG MEMPENGARUHI OPTIMALISASI PEMANFAATAN ASET TETAP PADA PEMERINTAH KOTA MATARAM - Siti Rahimah Nurdiana; Lilik Handajani; Alamsyah Alamsyah (Valid: Jurnal Ilmiah, 2016)
The purpose of this study was to examine and provide empirical evidence about the Effect of asset inventory, legal audit of assets, asset valuation and monitoring and control of assets to optimize the utilization of fixed assets belonging to the City of Mataram. Sampling using purposive sampling method, with the respondent amounted to 73 people, namely the administrator of goods and the echelon IV in each SKPD in Mataram. This study uses multiple regression data analysis tools.The results showed empirical evidence that the asset inventory, monitoring and control of assets has positive influence on optimizing the utilization of fixed assets of the City of Mataram. However, legal audit of assets and asset valuation does not affect the optimization of asset utilization. The study's findings indicate that the better the inventory as well as the supervision and control of the asset, then the more optimal utilization of fixed assets, other indications explained that the City of Mataram is still yet maximum in conducting legal audit of assets and the valuation of assets due to constrained problems of legality. The implications of this study lead to the need for accountability in the management of government-owned assets in order to improve the optimization of the utilization of fixed assets owned by the Government. Thus assets owned area can be more efficiently and provide potential revenue for the government, further the need for enforcement efforts to maintain the security of assets and ownership of assets owned